2001
DOI: 10.1038/sj.bjp.0704390
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of P‐glycoprotein mediated apical to basolateral transport of flunisolide in human broncho‐tracheal epithelial cells (Calu‐3)

Abstract: 1 Transepithelial transport of¯unisolide was studied in reconstituted cell monolayers of Calu-3, LLC-PK1 and the MDR1-P-glycoprotein transfected LLC-MDR1 cells. 2 Flunisolide transport was polarized in the apical (ap) to basolateral (bl) direction in Calu-3 cells and was demonstrated to be ATP-dependent. In LLC-MDR1 cells,¯unisolide was transported in the bl to ap direction and showed no polarization in LLC-PK1 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 40 publications
0
31
1
Order By: Relevance
“…[15][16][17][18] Recently, evidence of a P-gp-mediated assymetric drug transport in the airway epithelial cell line Calu-3 was demonstrated. 11,19 However, the results regarding the direction of the polarized efflux was contradictory between the studies. The functional effect of efflux transporter activity on the transport of drugs across the lung barrier in vivo has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 91%
“…[15][16][17][18] Recently, evidence of a P-gp-mediated assymetric drug transport in the airway epithelial cell line Calu-3 was demonstrated. 11,19 However, the results regarding the direction of the polarized efflux was contradictory between the studies. The functional effect of efflux transporter activity on the transport of drugs across the lung barrier in vivo has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 91%
“…46 Western blot analysis however revealed that cell line expresses P-gp. 39,40,42,47 Functional studies in Calu-3 layers using rhodamine 123, 40 cyclosporine 47 and digoxin 9 as P-gp substrates showed a polarised transport in the basolateral to apical (B-A) direction, indicating an apical localisation of the efflux pump on the cell membrane. By contrast, P-gp was localised in immunofluorescence on the basolateral side of the cell layer and flunisolide transport was enhanced in the absorptive direction in the study by Florea et al 39 Those conflicting results can likely be explained by differences in cell culture conditions and by the use of nonspecific P-gp substrates and inhibitors.…”
Section: P-gp In Respiratory Cell Culture Models In Vitromentioning
confidence: 99%
“…39,40,42,47 Functional studies in Calu-3 layers using rhodamine 123, 40 cyclosporine 47 and digoxin 9 as P-gp substrates showed a polarised transport in the basolateral to apical (B-A) direction, indicating an apical localisation of the efflux pump on the cell membrane. By contrast, P-gp was localised in immunofluorescence on the basolateral side of the cell layer and flunisolide transport was enhanced in the absorptive direction in the study by Florea et al 39 Those conflicting results can likely be explained by differences in cell culture conditions and by the use of nonspecific P-gp substrates and inhibitors. By using GF120918a, a highly potent and more selective P-gp inhibitor, 48 Madlova et al 9 measured a P-gp mediated polarised digoxin transport in the B-A direction only in Calu-3 cell layers at passages over 50 grown for three weeks on cell culture inserts.…”
Section: P-gp In Respiratory Cell Culture Models In Vitromentioning
confidence: 99%
“…Initially discovered in tumour cells while investigating the multidrug resistance mechanism, it has been also found and studied in many nontumour cells/tissues (Montano et al, 1996;Smit et al, 1998;Dautrey et al, 1999;Jonker et al, 1999;Gutmann et al, 2000;Florea et al, 2001;Batetta et al, 2003;Cisternino et al, 2003;Goralski et al, 2003;Elliott et al, 2004). P-gp indeed is involved in all pharmacokinetic events (Varma et al, 2003) and many single-nucleotide polymorphisms in the MDR1 gene have been correlated with differences in individual drug responsiveness (Marzolini et al, 2004).…”
Section: Introductionmentioning
confidence: 99%